Kemampuan Pemecahan Masalah Materi Pecahan Senilai Ditinjau dari Pemahaman Konsep dan Adversity Quotient (AQ) - Putri Ardila Nurvitasari; Matsuri Matsuri Matsuri; Septi Triyani Triyani (Didaktika Dwija Indria, 2026)
This study aimed to determine the relationship between conceptual understanding and Adversity Quotient (AQ) and the mathematical problem-solving ability regarding fractions among fourth-grade students in the Sriwijaya Kartasura Cluster. A quantitative approach with a correlational design was employed, using fourth-grade students from SDN schools in the Sriwijaya Kartasura Cluster as the research population. Data were collected using essay tests to measure conceptual understanding and problem-solving ability, and a questionnaire to measure Adversity Quotient (AQ). Data analysis was conducted using SPSS 27, utilizing Pearson Product-Moment correlation and multiple correlation techniques. The results revealed a positive and significant relationship between conceptual understanding and problem-solving ability (r = 0.666), a positive and significant relationship between Adversity Quotient (AQ) and problem-solving ability (r = 0.608), and a positive and significant relationship between conceptual understanding and Adversity Quotient (AQ) combined and problem-solving ability (R = 0.689). These findings indicate that better conceptual understanding and a higher Adversity Quotient (AQ) are associated with improved student ability to solve mathematical problems involving fractions.